Od postaci do głosu. O librettyzacji współczesnego dramatu - Karasińska, Marta (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The analyses presented in the article reverse the traditional course of studies which assume that the poetics of a dramatic text is instrumentally superior to that of the libretto. In order to adapt the hypothesis that contemporary drama is increasingly libretto-like, inserted into its structure is, excerpted by opera theatre researchers, the libretto poetics treated as a genealogical directive specific to the genre which differentiates it from the “third kind” in its classical expressions. The breakup of the basic categories constituting a drama ( character, dialogue and plot ) brings it visibly closer to the traditional operatic libretto with features characterised by Albert Gier, among others. The post-dramatic aesthetics adapted by contemporary opera and drama, which removes the character or reduces it to a voice treated merely as a medium, absolutising the way a word sounds and the poetics of a transsystemic remix all result in the emergence of a common aesthetics of the stage chimaera genre.